Improving the Power of GWAS and Avoiding Confounding from Population Stratification with PC-Select. Issue 3 (1st July 2014) - Tucker, George; Price, Alkes L; Berger, Bonnie
Abstract: Using a reduced subset of SNPs in a linear mixed model can improve power for genome-wide association studies, yet this can result in insufficient correction for population stratification. We propose a hybrid approach using principal components that does not inflate statistics in the presence of population stratification and improves power over standard linear mixed models.